1987
DOI: 10.3109/00365548709032386
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Norfloxacin on Human Oropharyngeal and Colonic Microflora and Multiple-dose Pharmacokinetics

Abstract: 10 healthy volunteers received 200 mg norfloxacin orally every 12 h for 7 days. Saliva, throat and faecal specimens were collected days 0, 3, 5, 7, 14 and 21 to study the effect of norfloxacin on the normal microflora. The concentrations of norfloxacin in serum, urine, saliva and faeces were determined by a microbiological method and all samples except faeces were also assayed by high-pressure liquid chromatography (HPLC). The pharmacokinetics of norfloxacin were studied on day 3. The mean peak serum concentra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
12
0

Year Published

1988
1988
2000
2000

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(16 citation statements)
references
References 16 publications
4
12
0
Order By: Relevance
“…De Vries-Hospers, Welling & van der Waaij (1985) found that, in ten human volunteers, daily oral treatment with 200 mg, 400 mg or 800 mg norfloxacin resulted in Enterobacteriaceae-free stool cultures after 3-5 days. A similar period of norfloxacin treatment was required for negative stool cultures in another study by Pecquet and co-authors (1985) as well as by Edlund et al (1987). In our pigs, it also took 5 or 3 days of treatment with the dosages used (400 mg/day and 800 mg/day respectively) before their stools were negative.…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…De Vries-Hospers, Welling & van der Waaij (1985) found that, in ten human volunteers, daily oral treatment with 200 mg, 400 mg or 800 mg norfloxacin resulted in Enterobacteriaceae-free stool cultures after 3-5 days. A similar period of norfloxacin treatment was required for negative stool cultures in another study by Pecquet and co-authors (1985) as well as by Edlund et al (1987). In our pigs, it also took 5 or 3 days of treatment with the dosages used (400 mg/day and 800 mg/day respectively) before their stools were negative.…”
Section: Discussionsupporting
confidence: 70%
“…In the studies of human subjects by De Vries-Hospers, Welling & van der Waaij (1985), the average faecal norfloxacin concentration during treatment with 200 mg, 400 mg and 800 mg per day was higher than we found in the pig. Also Gilfillan, Pelak & Bland (1984) as well as Edlund et al (1987) also reported relatively high average concentrations of 700-1000 mg/kg of faeces at the third day of treatment with 400 mg per day. Pecquet and co-authors (1985), also studying human volunteers, reported even higher concentrations between 1000 and 5000 mg/kg of faeces with a mean of 2500 mg/kg during treatment with 200 mg norfloxacin per day and 4000 mg/kg faeces during daily administration of 400 mg.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…After i.v. injection of NFLX, the elimination halflife (T 1/2β ) of 3.37 ± 1.37 hr in this study was similar to half-lives reported for mice, rats, dogs and monkeys [5], but shorter than the half-lives reported for horses [7], calves [13] and human beings [2]. The systemic clearance (Cl B ) of NFLX was 0.68 ± 0.18 l/kg/hr and the volume of distribution of NFLX at steady state (VD ss ) was 2.21 ± 1.07 L/kg.…”
supporting
confidence: 86%